Records Committee review for rare bird sighting of Lesser Black-backed Gull at Red Rock Reservoir Dam, 1984 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1984)
Records Committee review for a Lesser Black-backed Gull at Red Rock Reservoir Dam in Marion County, IA on December 3, 1984. Includes a record review document with votes, an article in Iowa Bird Life, and nine documentation forms submitted to the committee. Epson - sheet feed